Educational Policy and the Cultural Politics of Race: Introduction to the Special Issue. (January 2016) - Dumas, Michael J.; Dixson, Adrienne D.; Mayorga, Edwin
In this introduction to the special issue, the editors argue that struggles over the meaning(s) of race inform and are informed by educational policy deliberation and implementation. Educational policy, then, contributes to the "common sense" about race. At the same time, educational policy reflects, and is an instantiation of, that "common sense." The editors explain how the analyses offered in this special issue serve to expand what it means to do critical policy research, and more specifically, enhance our understanding of how race acts as a powerful force in determining educational opportunities, experiences, and outcomes.